The challenge of assessing multiple stressors in freshwater ecosystems: nonintuitive interactions between pesticide exposure and larval crowding - Bilbo, Tom R.; Dawson, Dan E.; Salice, Christopher J. (Frontiers in Freshwater Science, 2024)
It is widely recognized that populations of freshwater aquatic organisms are faced with a myriad of co-occurring stressors. These likely include manufactured chemicals, stressors due to climate change, habitat alterations, water quality parameters, etc. Importantly, these stressors are superimposed over "natural" stressors such as density of conspecifics. Density effects, in particular, are important and can result from resource competition or crowding; here we define crowding as high density but without resource limitation. Crowding has received less research attention despite its potential ecological importance and frequency of occurrence. In larval mosquitoes, for example, both physical and chemical components are important effects of crowding, which result in increased mortality, prolonged development, and reduced size. The objective of this research was to determine how different crowding conditions would affect subsequent insecticide sensitivity using the yellow-fever mosquito, Aedes aegypti. We hypothesized that stress due to crowding in the larval stage would increase insecticide sensitivity. Results showed that when larvae were reared at various crowding densities (without resource competition) but later exposed to a contact insecticide (permethrin) at equal densities they exhibited similar sensitivity. However, when larvae were reared at equal densities but exposed at various crowding densities there appeared to be a protective effect of crowding, as more densely crowded larvae were significantly less sensitive to the insecticide. Possible mechanisms for this protective effect were investigated. Induced detoxification enzymes do not appear to be a factor, but density-modified larval exposure is likely a mechanism. This research provides important insights into how mosquitoes may respond to control efforts as well as providing empirical recommendations on designing laboratory toxicity tests to better reflect ecological conditions in natural mosquito populations.